Mathematical Concepts in 8 Traditional Games from Hulu Sungai Tengah, South Borneo - Atsnan, Muh. Fajaruddin; Gazali, Rahmita Yuliana; Dewi, Sarmina; Fajaruddin, Syarief (International Journal of Psychosocial Rehabilitation, 2020)
The rich regional culture in Indonesia has numerous potentials that might be benefitted for introducing the mathematical concept to the children. One of the cultural potentials that might be benefitted in the mathematical learning process is found in the traditional games. With regards to the statement, in the Province of South Borneo, specifically in the County of Hulu Sungai Tengah (HST), there have been at least 8 traditional games that might be integrated into the mathematical learning process within the elementary school degree, the junior high school degree and even the senior high school degree. The eight traditional games are Tali Ulai, Tali Sol, Kelereng Segitiga, Cuk-Cuk Bimbi, Daku, Kompak Gambar, Asin and Dasprak Lingka. Within these games, the mathematical concepts such as odd and even numbers, summation, inequalities, parabole, linear line, two linear lines, angle and measurement with units of length, forecast, gain, loss, break even, node, line, plane, probability, multiplication as repetitive summation, division as repetitive subtraction, sets, rectangle, congruency, congruency in two planes, quadrant and ratio. Through these games, the children might be made familiar toward numerous mathematical concepts so that they might appreciate the usefulness of Mathematics in the daily life.